Atomic resolution studies of S1 nuclease complexes reveal details of RNA interaction with the enzyme despite multiple lattice‐translocation defects. Issue 10 (27th September 2022) - Adámková, Kristýna; Koval', Tomáš; Østergaard, Lars H.; Dušková, Jarmila; Malý, Martin; Švecová, Leona; Skálová, Tereza; Kolenko, Petr; Dohnálek, Jan
Abstract : Differences between the binding of RNA and DNA in S1 nuclease were analysed using X‐ray crystallography. In order to properly interpret the obtained diffraction data, a correction for multiple lattice‐translocation defects was applied. Abstract : S1 nuclease from Aspergillus oryzae is a single‐strand‐specific nuclease from the S1/P1 family that is utilized in biochemistry and biotechnology. S1 nuclease is active on both RNA and DNA but with differing catalytic efficiencies. This study clarifies its catalytic properties using a thorough comparison of differences in the binding of RNA and DNA in the active site of S1 nuclease based on X‐ray structures, including two newly solved complexes of S1 nuclease with the products of RNA cleavage at atomic resolution. Conclusions derived from this comparison are valid for the whole S1/P1 nuclease family. For proper model building and refinement, multiple lattice‐translocation defects present in the measured diffraction data needed to be solved. Two different approaches were tested and compared. Correction of the measured intensities proved to be superior to the use of the dislocation model of asymmetric units with partial occupancy of individual chains. As the crystals suffered from multiple lattice translocations, equations for their correction were derived de novo . The presented approach to the correction of multiple lattice‐translocation defects may help to solve similar problems in the field of protein X‐ray crystallography.